1960
DOI: 10.1103/revmodphys.32.445
|View full text |Cite
|
Sign up to set email alerts
|

Energy Levels ofF2andF2+<

Abstract: F we calculate to the same degree of approximation &~t he electronic energy levels of a molecule and of its ion, we are able (1) to obtain an extensive insight into the adiabatic potential curves, (2) to avoid arguments concerning physically meaningless results, and(3) to evaluate the ionization potential, the energies of the states in the Rydberg region, and other quantities having experimental importance.Fluorine has the following characteristics as compared with the other second-row elements. The ratio of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Molecules containing two or more electronegative atoms have generally provided significant challenges to attempts to provide a theoretical basis for understanding their chemistry or extending knowledge of their properties. This challenge first became apparent when Hijikata showed that F 2 was not bound in the Hartree−Fock approximation, a result which has been duplicated for a number of molecules containing F and Cl. Although Das and Wahl were able to obtain good results using a carefully selected multiconfiguration wave function, accurate results from a reasonably systematic approach were not obtained until it was possible to carry out complete active space (CAS) SCF and large scale multireference CI (MRCI) treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules containing two or more electronegative atoms have generally provided significant challenges to attempts to provide a theoretical basis for understanding their chemistry or extending knowledge of their properties. This challenge first became apparent when Hijikata showed that F 2 was not bound in the Hartree−Fock approximation, a result which has been duplicated for a number of molecules containing F and Cl. Although Das and Wahl were able to obtain good results using a carefully selected multiconfiguration wave function, accurate results from a reasonably systematic approach were not obtained until it was possible to carry out complete active space (CAS) SCF and large scale multireference CI (MRCI) treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The F 2 molecule represents a weakly bound system, and the Hartree−Fock-level PECs, at either the RHF or UHF level, are purely repulsive. , In reaction 5, this reactant molecule, as well as the transition complex HF 2 (TS), shows the largest MR effect among the systems considered in this work (cf. Table ).…”
Section: Resultsmentioning
confidence: 99%
“…At the UHF level it is not even bound. 25 Nonetheless, the dynamical correlation in F 2 is appreciable. In fact, the full valence space CAS SCF yields only half of the binding energy.…”
Section: B the F 2 Moleculementioning
confidence: 99%